Effects of Circuit Resistance Training with Crocus Sativus (Saffron) Supplementation on Plasma Viscosity and Fibrinogen - Abbass Ghanbari-Niaki; Ayoub Saeidi; Mahdi Aliakbari-Beydokhti; Sadegh Ardeshiri; Sarkawt Kolahdouzi; Mohammad Javad Chaichi; Bijan Hedayati-Monfared (The Society of Aging and Physical Activity (SAPA), 2015)
A limited number of studies has been carried out concerning the combined effects of resistance training and saffron supplementation on cardiovascular risk factors. The aim of this study was to assess the effects of circuit resistance training with Crocus sativus (saffron) supplementation on plasma viscosity and fibrinogen. For this purpose, 44 healthy male subjects, based on individual characteristics and after homogenization, were divided into four groups, including water-training (WT n=11), petal sweat-training (PST n=10), bottom part of flower-training (BFT n=11), and upper part of flower-training (UFT n=12). Resistance training consisted of 12 stations (each station for 30 seconds with 40% of one repetition maximum) for 2 weeks (5 sessions per week). Saffron in the amount of 500 mg was used twice daily, i.e. in the morning and immediately after exercise. Blood samples were taken before and 48 hours after the last exercise session and were analyzed for fibrinogen and plasma viscosity. Significant differences were observed between groups in plasma levels of fibrinogen (P=0.01). The post hoc test showed significant differences between the UFT and PST groups and the UFT and BFT groups (respectively, P=0.04 and P=0.014). In the post-test, plasma fibrinogen had significantly decreased in the WT (P=0.005), PWT (P=0.003), and UFT (P=0.001) groups compared with pre-test data (within group difference). Moreover, plasma viscosity was significantly changed among groups (F3, 37=3.52, P=0.024). The post hoc test showed significant differences between the UFT and WT groups (P=0.037). In post-test data, plasma viscosity had significantly decreased in the WT (P=0.015) and UFT (P<0.001) groups compared with pre-test data. The present results show that circuit resistance training with saffron supplements can reduce cardiovascular risk factors (fibrinogen and plasma viscosity).